Implementasi Pajak Progresif Bagi Kendaraan Roda Empat di Kota Makassar - Dara Amandah; Nur Hidayah; Aryanti Rezky Pratiwi (Fakultas Hukum, Universitas Sawerigading Makassar, 2025)
Four-wheeled Motor Vehicle Tax is one type of tax in Makassar City based on Law Number 28 of 2009 concerning Regional Taxes and Regional Levies and South Sulawesi Governor Regulation Number 90 of 2018 concerning Special Regional Taxes for Motor Vehicle Tax and Motor Vehicle Title Transfer Fee. This policy is stipulated in South Sulawesi Provincial Regulation No. 90 of 2018 concerning Special Regional Taxes for Motor Vehicle Tax and Motor Vehicle Title Transfer Fee. Based on the results of the analysis regarding the provisions for the implementation of the progressive tax for four-wheeled vehicles, it can be explained that there is a strong indication of progressive tax avoidance by taxpayers. This is evident from the continued decrease in the total revenue from four-wheeled vehicle tax after the progressive tax was implemented from 2018-2021. This is because, when the progressive tax was imposed, the progressive tax collection rate was considered too high by the public due to the large tax amount that had to be paid. Consequently, people purchase vehicles without putting them in their own names..